Psychodynamic-Interpersonal Supervision of Liu's Case of TC - Mednikov, Masha (Pragmatic Case Studies in Psychotherapy, 2007)
This commentary describes my observations as the clinical supervisor of Emily Liu's therapy with the case of TC. In line with my psychodynamic-relational perspective, I describe a major theme from the supervision: the emphasis upon the client-therapist relationship, with a focus on how Liu could first work with the steady stream of negative, off-putting interpersonal behaviors that TC initially manifested and then with the erotically tinged feelings that the client later showed in the therapy. In addition, I focus on two critical choice points: first, when Liu switched the positioning of the chairs, giving the client the option of regulating the amount and duration of the eye contact; and second, when Liu began to address the interpersonal dynamics with the client openly and directly. Finally, I consider some of the special cultural complexities in a case where the client and therapist, while Chinese American immigrants with a common cultural background, also diverge in many important ways, such as differences in dialect and language, in country of origin, in time in the United States, in English proficiency, and in the experience of racism within the ethnic community.